Regulatory role and mechanism of the inhibition of the Mcl-1 pathway during apoptosis and polarization of H37Rv-infected macrophages. Issue 42 (16th October 2020) - Han, Ling; Lu, Yang; Wang, Xiaofang; Zhang, Shujun; Wang, Yingzi; Wu, Fang; Zhang, Wanjiang; Wang, Xinmin; Zhang, Le
Abstract: Background: Myeloid cell leukemia-1 (Mcl-1) plays an important role in the clearance of Mycobacterium tuberculosis (MTB) infection. It has the effect of anti-apoptosis, protecting macrophages that have engulfed pathogens and preventing pathogen clearance. Meanwhile, the MAPK signaling pathway plays a significant role in regulating Mcl-1 expression during tuberculosis infection. In the case of latent infection and active infection, the apoptosis and polarization of macrophages have a great influence during MTB infection, so we discussed the effect of Mcl-1 on apoptosis and polarization. Then, further discussed its mechanism. Methods: An infected RAW264.7 macrophage model was established to investigate the regulatory role and mechanism of the Mcl-1 pathway inhibition during apoptosis and polarization of H37Rv infection. First, Mcl-1 protein and mRNA was identified by western blotting and Real-Time Polymerase Chain Reaction (RT-PCR). RAW264.7 macrophage apoptosis was detected by flow cytometry. RT-PCR was utilized to detect Bax, Caspase-3, Cyt-c and Bcl-2 mRNA expression. Next, Then the expression levels of inflammation factors CD86, CD206, iNOS, Fizz1, IL-6, IL-10, TNF-α, and TGF-β was detected by ELISA. SEM was used to observe macrophages phenotype. Finally, Bax, Bcl-2 and Bcl-xl the expression was detected by western blotting. Confocal microscopy was used to analyze mitochondrial membrane potential using the JC-10 kit. Results: In this study, we found that inhibiting the Mcl-1 expression signaling pathway led to infection by different virulence Mycobacterium tuberculosis, as well as changes in Mcl-1 protein and mRNA expression. Concomitantly macrophage apoptosis rate also changed, While, two phenotypic states of M1 and M2 appeared in the infected cells. We also found that the mitochondrial pathway was activated, the expression of its related genes Bax, casepase3, and Cyt-c, increased, whereas that of Bcl-2 decreased, and the mitochondrial membrane depolarization function was changed. Conclusions: We found that Mcl-1 affected the apoptosis and polarization of macrophages infected by Mycobacterium tuberculosis, mainly M1 in the early stage and M2 in the later stage. In addition, mitochondria played a crucial role in this process.